Intersecting disadvantages for married adolescents: Life after marriage pre- and post-COVID-19 in contexts of displacement - Baird, Sarah; Murphy, Maureen; Seager, Jennifer; Jones, Nicola; Malhotra, Anju; Alheiwidi, Sarah; Emirie, Guday; Rashid, Sabina; Sultan, Maheen (Elsevier, 2024)
This article was published in The Journal of Adolescent Health [©2022 Rights managed by Elsevier] and the definite version is available at: https://doi.org/10.1016/j.jadohealth.2021.12.001 The Article's website is at: https://www.sciencedirect.com/science/article/pii/S1054139X21006431?via%3Dihub